Active vibration control of functionally graded piezoelectric material plate. (1st January 2019) - Li, Jinqiang; Xue, Yu; Li, Fengming; Narita, Yoshihiro
Abstract: The present paper is concerned with active vibration control of functionally graded piezoelectric material (FGPM) plate using the piezoelectric material component as actuator. Using the classical laminated plate theory, the equation of motion for the FGPM plate is deduced based on Hamilton's principle and Rayleigh-Ritz method. A velocity feedback control method is used to obtain an effective active damping in the vibration control. The influences of distribution type, volume fraction index and total volume fraction of piezoelectric material on the vibration control of FGPM plate are investigated. The calculation results show that the vibration control result is strongly affected by the distribution of piezoelectric materials in FGPM plate. It is also found that the total volume fraction, especially the volume fraction index play an important role in the vibration control. Furthermore, under the non-uniform electric field the effect of external voltage position on active vibration control is studied. The results show that one can obtain an excellent control effect by optimizing the structure of FGPM plate and the position of external control voltage.